LECTURER’S ROLES AND INSTRUCTIONS IN PROMOTING STUDENTS’ READING MOTIVATION - Hajar, Siti; Supardi, Iwan; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: A great deal of (independent) learning in higher education involves reading; students? reading motivation is therefore especially important in learning. The current study thus aimed to find out what kind of lecturer?s roles and instructions does the lecturer use in motivating students to read in a sample of 5 students in Academic Reading/Vocabulary Class B and a lecturer. Lecturer?s roles and instructions in regard to the promotion of reading were assessed by classroom observations, to determine the actual classroom practices. Following these observations, students were interviewed using a conversational or semi structured interview. The lecturer was also interviewed in the same manner. The results revealed that the lecturer?s roles and instructions that promote students? reading motivation are in the forms of embedded values in reading, creating a safe learning environment, supporting real-world interactions, providing interesting texts, giving strategy instruction, giving opportunity to communicate conceptual understanding, and supporting students? collaboration. Keywords: Reading Motivation, Lecturer?s Role, Lecturer?s Instruction Abstrak: Membaca merupakan hal utama pada pembelajaran di perguruan tinggi, sehingga motivasi membaca menjadi hal penting yang harus dimiliki mahasiswa. Oleh karenanya, penelitian ini bertujuan untuk menemukan apa saja peran dan instruksi yang digunakan oleh seorang dosen untuk memotivasi mahasiswa untuk membaca. Objek pada penelitian ini adalah 5 orang mahasiswa dan seorang dosen pada perkuliahan Academic Reading/Vocabulary di kelas B. Peran dan instruksi dosen tersebut diukur dengan melakukan observasi yang bertujuan untuk melihat langsung proses perkuliahan. Bersamaan dengan itu, mahasiswa dan dosen diwawancara dengan menggunakan conversational atau semi structured interview. Hasil dari penelitian ini menyatakan bahwa peran dan instruksi yang digunakan dosen untuk memotivasi mahasiswa membaca adalah dengan menanamkan nilai-nilai akan pentingnya membaca, menciptakan suasana kelas yang aman, mendukung interaksi nyata dengan objek yang dibaca, menyediakan teks yang menarik, mengajarkan strategi-strategi dalam membaca, memberi kesempatan untuk mengkomunikasikan pemahaman mahasiswa mengenai teks yang dibaca, serta mendukung mahasiswa untuk berkolaborasi saat membaca. Kata kunci: Motivasi Membaca, Peran Dosen, Instruksi Dosen